Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

On Semeai Detection in Monte-Carlo Go. - Graf, Tobias; Schäfers, Lars; Platzner, Marco (Proceedings of the International Conference on Computers and Games (CG))

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Laemmle, Benjamin; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Weigel, Robert; Koelpin, Alexander; Kissinger, Dietmar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz f T SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm 2 . The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P 1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P 1dB of -17 dBm.

Integrator and digitizer for a non-coherent IR-UWB receiver - Digel, Johannes; Masini, Michelangelo; Grözing, Markus; Berroth, Manfred; Fischer, Gunter; Olonbayar, Sonom; Gustat, Hans; Scheytt, Christoph (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Impulse-radio ultra-wideband systems (IR-UWB) provide short-range wireless communication and precise localization simultaneously. Especially non-coherent IR-UWB reduces the system complexity which enables the design of low-power receivers. This paper presents an integrating digitizer which integrates rectified baseband pulses of an IR-UWB signal and provides the digitized data to the digital baseband of the receiver. The integrator is composed of two time-interleaved (TI) operational amplifiers with capacitive feedback. With this structure, the integrator can be periodically reset without introducing a dead time between two integration periods. The analog-to-digital conversion is performed by a 6 bit 62.4 MS/s successive approximation register analog-to-digital converter (SAR ADC). The integrating digitizer chip is realized in a 250 nm SiGe:C BiCMOS technology from IHP.

A low-cost miniature 120GHz SiP FMCW/CW radar sensor with software linearization - Sun, Yaoming; Marinkovic, Miroslav; Fischer, Gunter; Winkler, Wolfgang; Debski, Wojciech; Beer, Stefan; Zwick, Thomas; Girma, Mekdes Gebresilassie; Hasch, Jürgen; Scheytt, Christoph (Solid-State Circuits Conference Digest of Technical Papers (ISSCC), 2013 IEEE International)
This paper presents an integrated mixed-signal 120GHz FMCW/CW radar chipset in a 0.13μm SiGe BiCMOS technology. It features on-chip MMW built-in-self-test (BIST) circuits, a harmonic transceiver, software linearization (SWL) circuits and a digital interface. This chipset has been tested in a low-cost package, where the antennas are integrated. Above 100GHz, our transceiver has achieved state-ofthe-art integration level and receiver linearity, and DC power consumption.

Towards mm-wave System-On-Chip with integrated antennas for low-cost 122 and 245 GHz radar sensors - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Complex integrated 122 and 245 GHz SiGe BiCMOS transceiver ICs as well as an efficient broadband on-chip antenna are presented. The ICs target radar and sensing applications for the ISM bands at 122 and 245 GHz. Due to high level of integration and basic mm-wave self-testing production as well as test cost are dramatically reduced. Furthermore a compact and efficient on-chip antenna allows for chip-on-board mounting without RF interfaces.